W. A. Mozart first movement piano sonata kv 310 in a minor (2015)
With this work, we intend to make an approximation from the point of view of rhetoric and its figures to the sonata in the lower KV 310 of WA Mozart, which offers a series of explainable expressive resources from the oratory, which facilitate the understanding of music from a more intimate and personal perspective. Rhetoric, like the art of persuasion, then serves as a bridge to establish a connection between written music and affectivity, both of the performer and the listener.